2006
DOI: 10.1111/j.1464-410x.2006.06400.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis as a risk factor for benign prostatic hyperplasia

Abstract: OBJECTIVES To evaluate the relationship between clinical benign prostatic hyperplasia (BPH) and atherosclerosis, using colour Doppler ultrasonography (CDUS) and symptom scores. PATIENTS, SUBJECTS AND METHODS CDUS was used to evaluate prostatic vascularity in four groups of men, comprising young healthy subjects, patients presenting with coronary artery disease (CAD), diabetes mellitus, or peripheral arterial occlusive disease (PAOD). Resistive index (RI) measurements and computer‐assisted quantification of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 26 publications
(30 reference statements)
0
65
0
3
Order By: Relevance
“…6 Additionally, men with clinical cardiovascular disease/atherosclerosis or hypertension are at an increased risk for BPH development. 7 Damage to the vascular region of the prostatic transitional zone has shown an association with BPH in men with diabetes mellitus type II. 8 Advancing age is also associated with prostatic tissue remodelling, although this phenomenon has been reviewed mostly in BPH.…”
mentioning
confidence: 99%
“…6 Additionally, men with clinical cardiovascular disease/atherosclerosis or hypertension are at an increased risk for BPH development. 7 Damage to the vascular region of the prostatic transitional zone has shown an association with BPH in men with diabetes mellitus type II. 8 Advancing age is also associated with prostatic tissue remodelling, although this phenomenon has been reviewed mostly in BPH.…”
mentioning
confidence: 99%
“…In addition, McVary [11] has proposed four leading theories supporting biological plausibility that currently exist, namely, the nitric oxide synthase/NO theory; the autonomic hyperactivity and metabolic syndrome hypothesis; the Rho-kinase activation/endothelin pathway; and pelvic atherosclerosis. Berger et al [12] supported one of these theories that showed the relationship between an age-related impairment of blood supply to the lower urinary tract and pathogenesis of BPH. Although we did not evaluate ED patients for pelvic and penile vascular structures, there might be more severe vascular damage in patients with BPH and ED than without ED.…”
Section: Discussionmentioning
confidence: 89%
“…ED was diagnosed according to IIEF when total of IIEF-EF domain scores were < 26 points. The scoring of the IIEF-EF domain allowed classification of each patient as having no (26-30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16) or severe (1-10) ED. Adverse events were assessed at the end of the treatment course.…”
Section: Evaluation Proceduresmentioning
confidence: 99%
“…Hammarsten ve arkadaşları, AÜSS olan BPH hastalarında yaptıkları bir çalışmada diyabetik hastalarda olmayanlara göre daha hızlı yıllık prostat büyüme hızı olduğunu göstermişlerdir (9) . Koroner ve periferik arter hastalığının BPH ve AÜSS ile ilişkili olduğu birçok çalışmada gös-terilmiştir (4,5) . Robert ve arkadaşları, transüretral rezeksion veya açık prostatektomiden elde edilen prostat dokularında yaptıkları bir çalışmada, BPH hastalarında prostat dokusunda artmış makrofaj ve T-lenfosit infiltrasyonu olduğunu göstermişlerdir (10) .…”
Section: Discussionunclassified